Assessing of Some Toxic Heavy Metals Levels and Using Geo Accumulation Index in Sediment of Shatt Al-Arab and the Iraqi Marine Region (Baghdad Science Journal, 2019)
Mercury, arsenic, cadmium and lead, were measured in sediment samples of river and marine environmental of Basra governorate in southern of Iraq. Sixteen sites of sediment were selected and distributed along Shatt Al-Arab River and the Iraqi marine environment. The samples were distributed among one station on Euphrates River before its confluence with Tigris River and Shatt Al-Arab formation, seven stations along Shatt Al-Arab River and eight stations were selected from the Iraqi marine region. All samples were collected from surface sediment in low tide time. ICP technique was used for the determination of mercury and arsenic for all samples, while cadmium and lead were measured for the same samples by using Atomic Absorption Spectroscopy. The results for all the measurements in Shatt Al-Arab sediment showed the values at extent: (0.0611-0.1233 µg/g), (0.5490-46.2052µg/g), (2.3356-4.7773 µg/g), (51.3309-107.0358 µg/g) for concentration of mercury, arsenic, cadmium and lead respectively.While the concentrations in marine sediment were recorded at range: arsenic (0.3510 - 46.0110 µg/g), cadmium (3.5136 - 5.5905 µg/g) and lead (43.68974-75.37045µg/g). The statistical analysis for all stations was studied by using the software SPSS v-20.0. It shows there are no significant differences in the concentrations between stations at P≥0.05 level and also the geo accumulation index was calculated for metals in all stations.